Hybrid warfare and asymmetric security threats - Mitrović Miroslav (Војно дело, 2017)
Globalization with all its positive and negative effects, current events on the international scene, practice of international relations development, outbreak and management of conflicts around the globe, emergence of nonlinear and asymmetric forms of security threats, point to the existence and change of the developed forms of conflicts between states and non-state entities. On the one hand, we are witnesses that state and non-state entities in pursuing their interests are not guided by classical forms of conflict or warfare. At the same time, the effects of equipment and forces engagement lead to evident changes both in the sphere of real geopolitics in the field, as well as in the part of the divergence of the spheres of influence and gaining effects of strategic advantage and the positioning of influential global, and also regional powers. Therefore, the question arises: can the conduct of the conflict by unconventional means be a priori called asymmetric warfare, does it actually exist and what is the correlation of hybrid warfare with asymmetric security threats. This paper tends to summarize conceptual conditionality, diversity, as well as the harmonization of the two mentioned phenomena, in a concise form, by analyzing a broad theoretical base of scientific literature, normative acts and analytical documents, based on the analysis of generic conditions for the existence of asymmetric threats and hybrid warfare.